O "zepsutych aforyzmach" Anatolija Kima - Jastrzębska, Katarzyna; Mrózek, Alicja (Rusycystyczne Studia Literaturoznawcze, 2008)
The article concerns a selected aspect of Anatolij Kims works, a Russian prose writer belonging to the so called Moscow school. The authors of the article characterize the style of his writing, exemplifying it on such statements and expressions that can be referred to as the genre of aphorism or maxim. The examples presented in the article derive from both the novel, stories and short stories of the Russian prose writer. Also, in order to illustrate the characteristics of the genres under investigation, aphorisms by Stanis³aw Jerzy Lec were used in the analysis conducted.